DISEÑO DE UN PROGRAMA DE INCENTIVOS PARA LA AFILIACIÓN VOLUNTARIA A LA SEGURIDAD SOCIAL, DE LOS COMERCIANTES DE LAS FERIAS LIBRES DE LA CIUDAD DE LOJA, PERIODO 2019-2021 - Sanmartín Jiménez, Jonathan Rafael. (2019)
The research work was carried out in accordance with the structure provided by the Academic Regime Regulations of the National University of Loja. Constant review of the literature where theories and fundamental concepts are exposed for the preparation of the Program of incentives for voluntary affiliation. The purpose of the investigation is to Design an Incentive Program for Voluntary Social Security Affiliation, of the merchants of the free fairs of the City of Loja, period 2019-2021, for this, a diagnosis of the situation was made current social security of merchants, identifying the reality in which they are operating their activity and barriers, disincentives and incentives of social security that are located in the target population. Everything stated will be done through the information collected that includes young people, adults and seniors (18 years and older). To do this, once the basic information is obtained, the factors that affect the merchants do not opt for the voluntary affiliation that exists access barriers, the main factor being the economic one with a level of income of 20 to 200 dollars per month from the merchants. interposes to generate an affiliation. In the political factor it was determined that the traders have not chosen to belong to any social insurance because of the fact that the bureaucracy has not provided improvements in social services and finally the cultural factor determining the little interest they have towards the benefits of being affiliated preferring to devote himself only to his activity.